Factors affecting surgical decision-making in carriers of BRCA1/2 pathogenic variants undergoing risk-reducing surgery at a dedicated hereditary ovarian cancer clinic. Issue 2 (February 2022) - Jacobson, Michelle R.; Walker, Melissa; Ene, Gabrielle E.V.; Firestone, Courtney; Bernardini, Marcus Q.; Allen, Lisa; Huszti, Ella; Sobel, Mara
Abstract: Objective: Women with germline BRCA1/2 pathogenic variants have a significantly elevated lifetime risk of ovarian and fallopian tube cancer. Bilateral salpingo-oophorectomy (RRSO) is associated with a 90% reduction in the development of tubal and ovarian cancer. At our tertiary hospital, we have a dedicated clinic where women predisposed to hereditary ovarian/tubal cancer receive counseling on reproduction, risk reduction, surgical prophylaxis, and menopausal aftercare. The objective of this study was to evaluate the choices that Canadian women with BRCA1/2 pathogenic variants make regarding ovarian cancer risk reduction within this highly specialized multidisciplinary clinic. Methods: This retrospective chart review included all women with confirmed BRCA1/2 mutations referred to the Familial Ovarian Cancer Clinic at Women's College Hospital, Toronto, Canada over a 45-month time period. Patient demographics, preoperative consultation notes and investigations, intraoperative findings, and pathology were recorded. Results: A total of 191 women were included in our cohort; 140 (73.3%) underwent risk-reducing surgery and 51 (26.7%) deferred or declined surgery. In women who underwent surgical prevention (median age 45 [30-72] y), 123 (87.9%) underwent RRSO and 17 (12.1%) chose a risk-reducing bilateral salpingectomy with deferred oophorectomy. Of the women undergoing RRSO, 11 (8.9%) women chose concurrent hysterectomy. Prevalent themes affecting decision-making included fears around premature surgical menopause, family planning, and concerns around development of endometrial cancer related to tamoxifen. Conclusion: Women with BRCA1/ 2 pathogenic variants face challenging decisions regarding risk reduction and care providers must be knowledgeable and supportive in helping women make informed and individualized choices about their care. N/A: Video Summary: http://links.lww.com/MENO/A857 . Abstract : Supplemental Digital Content is available in the text